Environmental Performance and Executive Compensation: An Integrated Agency-Institutional Perspective - Berrone, Pascual; Gomez-Mejia, Luis R. (Academy of Management Journal, 2009)
Relying on institutional theory, agency rationale, and environmental management research, we hypothesize that, in polluting industries, good environmental performance increases CEO pay; that environmental governance mechanisms strengthen this linkage; that pollution prevention strategies affect executive compensation more than end-of-pipe pollution control; and that long-term pay increases pollution prevention success. Using longitudinal data on 469 U.S. firms, we found support for three hypotheses. Contrary to our expectations, firms with an explicit environmental pay policy and an environmental committee do not reward environmental strategies more than those without such structures, suggesting that these mechanisms play a merely symbolic role.